Late Pleistocene to Mid-Holocene climate variability in Ireland : evidence from Ostracod geochemistry - McKenzie, Shawn Michael (2010)
Stable isotope values of ostracod calcite provide a record of variation in ¥ä18O(H2O) values and water temperature from the late glacial to mid-Holocene in Western Ireland. Lough Monreagh, located in County Clare, Western Ireland, contains marl sediment that includes pristine ostracod calcite whose ¥ä18O and ¥ä13C values were evaluated. These values were used relative to modern ecological requirements to derive a paleoenvironmental record for Lough Monreagh that includes water temperature, eutrophication, water depth, as well as terrestrial vegetation and weathering within the lake¡¯s watershed. ¥ä13C values of ostracod calcite presented herein suggest a significant increase in terrestrial vegetation beginning during the Aller©ªd (13,600 cal year B.P.) and extending through to the mid-Holocene (6,997 cal year B.P.). Marl and ostracod ¥ä18O values record variability in temperature and precipitation ¥ä18O(H2O) values that are in turn forced by variation in atmospheric and oceanic circulation. Water temperatures presented herein were calculated from ¥ä18O values of ostracod calcite and marl, constrained by temperature preference and tolerance ranges of ostracod species, yielding the highest resolution temperature record covering this period to date. Over 4,700 ostracods representing all three freshwater superfamilies were counted and identified to evaluate the trophic stage of the lake. The lake was characterized as a clear-, cold-water (~8¨¬C summer water temperature), low-nutrient environment during the Aller©ªd, then freezes abruptly during the Younger Dryas as evidenced by black clay deposits aged 12,800 to 11,300 cal yr B.P. Following the Younger Dryas, transitional warming and increasing terrestrial vegetation are evidenced by decreasing ¥ä13C values of ostracoda and faunal transition to phytophyllic species. Summer water temperatures warm to >16¨¬C, with ostracod species suggesting a shallow-water, fen- and macrophyte-rich environment with abundant plant life in and around the lake by ~8,000 cal yr B.P.